Son of God: reflections on a tradition - Bryan, Christopher (Oxford University Press, Incorporated, 2022)
What do Christians mean when they call Jesus "son of God"? In this study of the phrase "son of God" as applied to Jesus of Nazareth, Christopher Bryan examines the testimony of various New Testament witnesses who used this expression to speak of him, and asks where they got it from, what they meant by it, and how it might have been understood.